Philosophical reflections on Study in Chinese bamboo Flute in China - Shi Shou; Hirunrux , Sakchai; Sartjinpong, Nayos (Journal of Modern Learning Development, 2023)
In the early 1980s, the teaching of national instrumental music began to explore how to diversify and make teaching methods of national instrumental music scientific. Many researchers began to ponder the deep problems of bamboo flute teaching in expanding new thinking space and academic dimensions. Due to the rigidity of performance, teaching, and creation of national instrumental music for a long time and the repression of conservative ideas, it has been unable to find new ideological resources and thinking perspectives. It cannot produce a new thinking platform from the old teaching system. This article presents philosophical reflections on a study of the Chinese bamboo flute.